Pengembangan Multimedia Interaktif "SEHATI" sebagai Media Pembelajaran Sistem Peredaran Darah Manusia Kelas VIII SMP - Chelsea Dewantari (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Abstract. Science learning on the topic of the human circulatory system in Grade VIII junior high school is still predominantly conducted using textbooks and student worksheets, resulting in less interactive learning and limited student engagement. This study aimed to develop SEHATI (Human Circulatory System) interactive multimedia and identify students' responses to the developed learning media. The research employed the Research and Development (R&D) method using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The multimedia was developed using Canva and implemented as an interactive presentation based on Microsoft PowerPoint. Data were collected through a student response questionnaire administered to 15 eighth-grade junior high school students. The results showed that the SEHATI interactive multimedia achieved an average student response score of 3.50, which falls into the Very High category. The highest score (3.80) was obtained for the clarity and attractiveness of the images and illustrations, indicating that the multimedia effectively captured students' attention and supported their understanding of the learning material. Therefore, SEHATI has the potential to be used as an engaging learning medium to support science learning on the human circulatory system.